Dealing With Issues in Construction in The Area of Reclamation: Solution, Strategy & Implementation - Pratikso .; Soedarsono . (International Conference on Coastal and Delta Areas, 2015)
In this present day, cities with delta area have mostly been doing coastline reclamation. The main problem is that the soil of the reclamation has been suffering from great settlement due to consolidation what makes the buildings around become instable, this is because the landfill is done on the soft soil. Supposed that the consolidation is happening naturally as it is, this will run in a relatively longer time, years or even decades. In order to be stable, it needs longer time, as a consequency, soil is not able to be used fo building to which this will give damage in term of time and finance. That is why, engineering is needed to fasten the consolidation process in order to make the soil of reclamation able to be used efficiently. One of particular methods to fasten the consolidation process is by building vertical drain. There are many ways and materials that can be used to set up vertical drain, among which are by making small holes through drilling then this is filled up with porous materials such as sand and gravel stone or coir. In this recent days, new method has already been available to fasten the consolidation process by geosynthetic that is Prevabicated Vertical Drain made of polymer material. The use of geosynthetic for vertical drain can fasten the consolidation process significantly. The speed process of consoliatioon depends on the types of soil and model of the vertical drain as well as distance among holes. Vertical drain can only accelerate the settlement due to consolidation, but this does not minimize it. By applying the drain model, time for the soil settlement can possibly be arranged what makes the soil of reclamation be more ready for use.